Altered developmental trajectories for impulsivity and sensation seeking among adolescent substance users. (September 2016) - Charles, Nora E.; Ryan, Stacy R.; Bray, Bethany C.; Mathias, Charles W.; Acheson, Ashley; Dougherty, Donald M.
Abstract: A number of studies have associated impulsivity and sensation seeking with level of substance use and risk for developing a substance use disorder. These relationships may be particularly apparent during adolescence, when developmental changes in impulsivity and sensation seeking occur at the same time as increased opportunities for substance use. To examine this, the current study measured impulsivity and sensation seeking from pre-adolescence to mid-adolescence in a sample of youth, the majority of whom were identified as being at risk for developing a substance use disorder based on their family history of substance use disorders. Youth were separated into those who did ( n  = 117) and did not ( n  = 269) initiate substance use by mid-adolescence. Results showed that substance users were more impulsive and more sensation seeking during pre-adolescence, prior to any significant substance use, and that greater sensation seeking in pre-adolescence was related to heavier substance use by mid-adolescence. In addition, developmental trajectories for substance-using youth showed a greater increase in sensation seeking but a more modest decrease in impulsivity from pre-adolescence to mid-adolescence. Taken together, these results indicate that increased impulsivity and sensation seeking is apparent in adolescent substance users as early as pre-adolescence, that the difference between substance users and non-users becomes larger across early adolescence as their developmental trajectories diverge, and that greater sensation seeking in pre-adolescence may predict increased substance use by mid-adolescence. Highlights: We model the development of impulsivity and sensation seeking in youth age 11–15. Sensation seeking increased and impulsivity decreased as youth matured. Preadolescent impulsivity and sensation seeking were higher among substance users. Developmental trajectories for substance users and non-users differed.